Validation of Cymbasoma turcorum and Monstrillopsis pontoeuxinensis, two monstrilloids from Turkey described by Suárez-Morales & Üstün in 2018 (Crustacea: Copepoda: Monstrilloida) - Suárez-Morales, Eduardo; Üstün, Funda (Zootaxa, 2020)
Recently, Suárez-Morales & Üstün (2018) described two new species of monstrilloid copepods, Cymbasoma turcorum and Monstrillopsis pontoeuxinensis from Turkish coastal waters of the Black Sea. The morphological descriptions, illustrations, and type designations presented in that paper fully characterized both new species; however, the journal issue in which the description appeared was published only online, with no print version (Suárez-Morales & Üstün 2018), and the article in which these new names were introduced did not include a ZooBank registration number (LSID) for the article or any other evidence of such registration. This is currently required by Article 8.5 of the International Code of Zoological Nomenclature for an electronic work to be deemed “published” under the Code (International Commission on Zoological Nomenclature 2012). Inasmuch as Suárez-Morales & Üstün (2018) is an “unpublished work”, the specific names turcorum and pontoeuxinensis proposed in it are unavailable. The present note is intended to fully validate these two names by proposing them once again as new while also fulfilling all of the Code’s current conditions for nomenclatural availability of this work itself and the two new names. The date and authorship of these two specific names will, accordingly, be those of this note, not Suárez-Morales & Üstün (2018).